Rupee v/s Dollar-"The Double Edged Sword" - Gupta, Garima (Indian Journal of Finance, 2008)
Foreign exchange markets are the largest markets in the world and always remain volatile in nature. In such a market where cross currency buying and selling occurs and funds move from one option to another, one can face risk every time when one enters and trades in the market.Indian forex market has undergone many changes before growing into one of the major foreign exchange markets in the world. However risk has been an inherent part of forex markets across globe and Indian forex market has been no exception. One of the important factors that have contributed towards this uncertainty is the prevailing exchange rate of Re.v/s .The exchange rate has experienced several fluctuations and has been a major characteristic of Indian Forex market in recent times. Usually exchange rates are determined through the flow of capital between countries, rate of inflation, interest rates and confidence in the economy of respective country.